Sweetening the Deal: Investigating the Impact of Product Quality and Price on Honey Purchase Behavior at PT Kembang Joyo Sriwijaya, Malang - Imron Dwi Nursahid Nursahid; Fithri Mufriantie (Universitas Muhammadiyah Malang, 2023)
Consumer purchasing decisions are complex individual processes that involve numerous considerations before making a purchase. Product quality and price are two significant factors that influence consumer purchasing decisions. Understanding the influence of these factors is crucial for businesses seeking to improve their sales and meet the expectations of their customers. This study aims to investigate the impact of product quality and price on consumer purchasing decisions for honey at PT Kembang Joyo Sriwijaya Malang. The study employed a quantitative research design, using accidental sampling to select consumers who had purchased honey from the store more than once. Data was collected from 75 respondents, and structural equation modeling (SEM-PLS) was used to analyze the data. The analysis involved examining the relationship between product quality and price with consumer purchasing decisions. The findings of the study showed that product quality and price had a significant positive effect on consumer purchasing decisions. Product quality had a positive relationship with purchasing decisions, influencing 20.6% of the variance (path coefficient=0.206, t-statistic=2.410, p-value=0.016). Price had a stronger positive relationship, influencing 65.4% of the variance (path coefficient=0.654, t-statistic=10.534, p-value=0.000). These results suggest that both product quality and price are essential factors to consider when seeking to improve sales and meet customer expectations in the honey market at PT Kembang Joyo Sriwijaya Malang.